2013
DOI: 10.3892/or.2013.2717
|View full text |Cite
|
Sign up to set email alerts
|

3,3′-Diindolylmethane suppresses the growth of gastric cancer cells via activation of the Hippo signaling pathway

Abstract: Abstract. Recent studies have revealed that 3,3-diindolylmethane (DIM) has antitumor effects in both in vivo and in vitro tumor models. However, the biological function of DIM in human gastric cancer cells is unknown. Genetic and biological studies have confirmed the importance of the novel Hippo tumor-suppressor pathway in regulating cell proliferation, apoptosis, organ size and tumorigenesis in mammals. Thus, the purpose of this study was to investigate the cytotoxic effects of DIM in human gastric cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…However, these studies have predominantly involved the development of cancer (Lerner et al, 2012;Li et al, 2013). Similarly, studies have shown that miR-22 can protect against cancer as illustrated by the fact that overexpression of miR-22 is associated with reduced tumor growth, volume, and decreased migration of tumor cells (Ling et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies have predominantly involved the development of cancer (Lerner et al, 2012;Li et al, 2013). Similarly, studies have shown that miR-22 can protect against cancer as illustrated by the fact that overexpression of miR-22 is associated with reduced tumor growth, volume, and decreased migration of tumor cells (Ling et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the use of plant-derived indoles, such as 3,39-diindolylmethane (DIM), which are found in cruciferous vegetables, and other similarly structured compounds, have been reported as a potential therapeutic modality against inflammatory disorders (Busbee et al, 2013). Data from various cancer studies, which include prostate (Nachshon-Kedmi et al, 2003), colon (Lerner et al, 2012), and gastric (Li et al, 2013) cancers, have collectively suggested that DIM also acts on a number of molecular pathways centered on cellular proliferation and survival to mediate its effects. In contrast, the immunomodulatory and antiproliferative properties of DIM have not been well studied, particularly in regards to autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Turati et al (12) and Guercio et al (16) reported that high allium vegetable consumption reduces gastric cancer risk, and a high intake of cruciferous vegetables was found to be inversely associated with the risk of gastric cancer in humans in a study by Wu et al (15). The compound 3,3'-diindolylmethane (DIM) is a component of cruciferous vegetables that inhibits tumor growth through induction of apoptosis in various types of cancer cells (17)(18)(19)(20). Our previous study demonstrated that DIM suppressed gastric cancer cell growth via activation of the Hippo signaling pathway (17).…”
Section: Introductionmentioning
confidence: 99%
“…The compound 3,3'-diindolylmethane (DIM) is a component of cruciferous vegetables that inhibits tumor growth through induction of apoptosis in various types of cancer cells (17)(18)(19)(20). Our previous study demonstrated that DIM suppressed gastric cancer cell growth via activation of the Hippo signaling pathway (17). DIM was found to inhibit gastric cancer cell growth by modulating the aryl hydrocarbon receptor (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation